The politics and anti-politics of social movements: religion and AIDS in Africa - Patterson, Amy Stephenson; Burchardt, Marian; Mubanda Rasmussen, Louise (Routledge, 2016)
"This book explores the nature, significance and consequences of the religious activism surrounding AIDS in Africa. While African religion was relatively marginal in inspiring or contributing to AIDS activism during the early days of the epidemic, this situation has changed dramatically. In order to account for these changes, contributors provide answers to pressing questions. How does the entrance of religion into public debates about AIDS affect policymaking and implementation, church-state relations, and religion itself? How do religious actors draw on and reconfigure forms of transnational connectivity? How do resource flows from development and humanitarian aid that religious actors may access then affect relationships of power and authority in African societies? How does religious mobilization on AIDS reflect contestation over identity, cultural membership, theology, political participation, and citizenship? Addressing these questions, the authors draw on social movement theories to explore the role of religious identities, action frames, political opportunity structures, and resource mobilization in African religions’ reaction to the AIDS epidemic. The book’s findings are rooted in fieldwork conducted in Tanzania, Uganda, Zambia, Zimbabwe, Ghana, and Mozambique, among a variety of religious organizations. This book was originally published as a special issue of the Canadian Journal of African Studies."--Amazon